(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores the theoretical aspects of using utopian terms in literary texts and their contribution to revitalizing a work’s narrative structure. By examining the role of utopian concepts in literature, the study investigates how they influence readers’ perceptions, enhance thematic depth, and create immersive worlds. The paper also discusses the historical evolution of utopian terminology and its significance in modern literature.